Encyclopedia of politics, the media, and popular culture - Cogan, Brian 1967-; Kelso, Tony.; Gale Group (Santa Barbara, Calif. Greenwood Press, 2009)
Provides a sweeping survey of the historic and ongoing interplay between politics, the media, and popular culture.
Political movies -- Political documentaries -- Politics and radio -- Politics and television entertainment -- Entertaining news and political news satire -- Politics and popular music -- Political campaign advertising -- Politics online.
Electronic reproduction.
Keywords: Mass media -- Political aspects -- United States; Communication in politics -- United States; Popular culture -- Political aspects -- United States; Electronic books